Impact of inorganic iron and haem on the human gut microbiota; An in vitro batch-culture approach - Monteagudo-Mera, Andrea; Shalunkhe, Arvindkumar; Duhduh, Amro; Walton, Gemma E.; Gibson, Glenn R.; Pereira, Dora I.; Wijeyesekera, Anisha; Andrews, Simon C. (Frontiers in Microbiology, 2023)
Although iron is an essential nutrient for humans, as well as for almost all other organisms, it is poorly absorbed (~15%) from the diet such that most passes through the upper gut into the large intestine. The colonic microbiota is thus exposed to, and potentially influenced by, such residual iron which could have an impact on human health. The aim of the research described here is to determine how the major forms of dietary iron (inorganic iron and haem) influence metabolic activity and composition of the human gut microbiota by utilising an in vitro parallel, pH-controlled anaerobic batch culture approach. Controlled iron provision was enabled by the design of a ‘modified’ low-iron gut-model medium whereby background iron content was reduced from 28 to 5 µM. Thus, the impact of both low and high levels of inorganic and haem iron (18-180 µM and 7.7-77 µM, respectively) could be explored. Gut-microbiota composition was determined using next generation sequencing (NGS) based community profiling (16S rRNA gene sequencing) and flow-fluorescent in situ hybridisation (FISH). Metabolic-end products (organic acids) were quantified using gas chromatography (GC) and iron incorporation was estimated by inductively coupled plasma optical emission spectroscopy (ICP-OES). Results showed that differences in iron regime induced significant changes in microbiota composition when low (0.1% w/v) faecal inoculation levels were employed. An increase in haem levels from 7.7 to 77 µM (standard levels employed in gut culture studies) resulted in reduced microbial diversity, a significant increase in Enterobacteriaceae and lower short chain fatty acid (SCFA) production. These effects were countered when 18 µM inorganic iron was also included into the growth medium. The results therefore suggest that high-dietary haem may have a detrimental effect on health since the resulting changes in microbiota composition and SCFA production are indicators of an unhealthy gut. The results also demonstrate that employing a low inoculum together with a low-iron gut-model medium facilitated in vitro investigation of the relationship between iron and the gut microbiota.